2014
DOI: 10.3390/toxins6041177
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of Individual and Combined Effects of Ochratoxin A and Zearalenone on HepG2 and KK-1 Cells with Mathematical Models

Abstract: Ochratoxin A (OTA) and Zearalenone (ZEA) are widespread mycotoxins that contaminate foodstuffs simultaneously, but sufficient data regarding their mixed toxicities are lacking. This study aims to analyze the style of combined effects of OTA and ZEA on cells of their target organs. For this purpose, cytotoxicity was determined in HepG2 and KK-1 cells treated with single and combined forms of OTA and ZEA. Furthermore, we have analyzed the data using two mathematical models based on the concepts of concentration … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
36
0
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 50 publications
(42 citation statements)
references
References 53 publications
1
36
0
2
Order By: Relevance
“…These data suggest that cellular oxidative stress plays a critical role in the observed apoptosis. In previous studies, similar results were observed in HepG2 and porcine IPEC-J2 cells as ZEN generated ROS, reduced antioxidant enzyme activities, and induced cell death in vitro [24][25][26].…”
Section: Discussionsupporting
confidence: 82%
“…These data suggest that cellular oxidative stress plays a critical role in the observed apoptosis. In previous studies, similar results were observed in HepG2 and porcine IPEC-J2 cells as ZEN generated ROS, reduced antioxidant enzyme activities, and induced cell death in vitro [24][25][26].…”
Section: Discussionsupporting
confidence: 82%
“…The MDR and TI values indicated slight synergistic and antagonistic interactions among the components of the chemical mixtures. Nevertheless, the values are within 0.5 -2.0 range, thus the mixtures are said to be additive (Petersen & Tollefsen, 2011;Li et al, 2014).…”
Section: Resultsmentioning
confidence: 99%
“…This does not seem to be correct according to the dose-response curves for OTA (E (1.60 µM of OTA) ≈ 30%) and ZEN (E (23.68 µM of ZEN) ≈ 50%) presented in aforementioned article [44], which raises the question: can the observed synergies be trusted at all? Even though this model is mathematically valid, due to the excessive number of assumptions that need to be fulfilled, this model probably remains inapplicable for assessing combinations of mycotoxins [43].…”
Section: Loewe's Additivity Lawmentioning
confidence: 95%
“…Finding two mycotoxins in a combination that fulfils all of these assumptions seems somewhat impossible. For example, apart from the Bliss independence criterion, Li et al [44] also used this method (as a concentration addition model) to assess the nature of interaction between OTA and ZEN. Since their dose-effect curves did not meet all of the assumptions, it is easy to see that Equation 4, on which Loewe's additivity law is based, does not hold true when we assign the values EC 10 (OTA) = 0.8 µM and EC 10 (ZEN) = 11.84 µM [44], and try to apply the main principles of dose equivalence and sham combination of this model (Equations 7and 8…”
Section: Loewe's Additivity Lawmentioning
confidence: 99%